2022
DOI: 10.1021/acsaem.2c02724
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Controlled Strategy for High-Quality Single-Source Vapor-Deposited Cs2AgBiBr6 Thin Films

Abstract: Environmentally friendly lead-free Cs2AgBiBr6 double perovskites have emerged as potential materials for photovoltaic applications owing to their nontoxicity and high stability. However, the low solubility of precursors in the solution method and the deviated composition in the reported sequential evaporation process are still the challenges to obtain highly pure Cs2AgBiBr6 phase films. In this work, we proposed a single-source vapor deposition process for high-quality Cs2AgBiBr6 films with an effective therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Furthermore, the drawbacks of low selectivity and weak band alignment for HTM-free PVs are mitigated by the formation of the 2D/3D-mixed perovskite phase. Although our solar cells possess relatively low PCEs, which is a common problem for this material, [38,[41][42][43][44][45][46][47][48][49] there are promising reports of highly improved Cs 2 AgBiBr 6 , i.e., by hydrogenating the material, that will benefit from applying our approach to further boost such technology. [84]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the drawbacks of low selectivity and weak band alignment for HTM-free PVs are mitigated by the formation of the 2D/3D-mixed perovskite phase. Although our solar cells possess relatively low PCEs, which is a common problem for this material, [38,[41][42][43][44][45][46][47][48][49] there are promising reports of highly improved Cs 2 AgBiBr 6 , i.e., by hydrogenating the material, that will benefit from applying our approach to further boost such technology. [84]…”
Section: Discussionmentioning
confidence: 99%
“…[28,39,40] Also, the role of the Cs 2 AgBiBr 6 crystallization to form thin films for well-performing solar cells is still not understood: thin films of pristine Cs 2 AgBiBr 6 with comparable thicknesses and homogeneities result in reported solar cells with PCEs ranging from below 1% to above 2% despite equal solar cell architectures. [38,[41][42][43][44][45][46][47][48][49] Sirtl et al revealed in their work that low selectivity of the hole transport material (HTM) supports recombination and therefore hampers the solar cell performance, due to insufficient band alignment, i.e., the absence of an electron barrier between perovskite and HTM. [50] Thus, they exposed a critical bottleneck of Cs 2 AgBiBr 6 -based solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Halide perovskite (PVSK) materials are regarded as a promising solution to address energy and environmental challenges since the first demonstration in 2009 . Despite the noteworthy highest record of a power conversion efficiency (PCE) of 25.8% on lab-scale devices for the typical APbX 3 perovskite solar cells (PSCs), the environmental instability and lead toxicity have been major obstacles for their large-scale commercialization. , One viable strategy to resolve the toxicity is to replace the Pb content by nontoxic elements such as Sn and Ge, , while their susceptibility to oxidation leads to a more severe instability problem. , Alternatively, double perovskites with the form of A 2 B + B 3+ X 6 have been proposed for their better balance on these issues, among which Cs 2 AgBiBr 6 emerges as one highly regarded candidate with high open circuit voltage, low toxicity, and adjustable optoelectronic properties. What is more, the inherent high decomposition enthalpy of Cs 2 AgBiBr 6 enables its superior stability compared to other lead-free perovskites …”
Section: Introductionmentioning
confidence: 99%
“…It prompts the multi-layer film to form a one-layer film with a large grain size and also flattens the perovskite surface, obtaining an excellent result with a large grain size, high X-ray sensitivity, and low detection limit of the device. The whole process only lasts 5 min, which is 50% shorter than the other annealing times (10 min or longer) for Cs 2 AgBiBr 6 perovskites. Besides, by investigating the remaining chemical bond, the crystal lattice of the film, and the residual atom species, we attribute the excellent performance to the recrystallization of the small-sized grain (∼100 nm) and the removal of the impurity substance, which results from the slowing down of the residual solvent evaporation and suppressing of the halide volatilization .…”
Section: Introductionmentioning
confidence: 99%